Characterization of children younger than five years with suspected allergic diseases - Laura del Mar Vásquez; Manuela Olaya; Daniela Cleves; Luis Fernando Ramírez-Zuluaga; Carlos Serrano Reyes (Revista Alergia México, 2018)
Background: Symptoms of allergic diseases are a common cause of consultation during childhood.